Strategi Dakwah Muslimah di Perkotaan: Studi pada Komunitas Humaira Surakarta - Siti Zaida Hanum; Abraham Zakky Zulhazmi (Academic Journal of Da'wa and Communication, 2022)
This study aims to describe the da'wah strategy carried out by the Komunitas Humaira Surakarta. This community is one of the hijrah communities in Surakarta. This research is a qualitative descriptive study. The results showed that the Komunitas Humaira Surakarta based in urban areas held a number of programs to support their da'wah. The programs include Kajian Kamis, Kajian for Teens, Taklim for Kids, Program Sedekah Pondok Pesantren, Anak Asuh, Sembako Lansia Dhuafa, Humaira Mukena Bersih, Free Medical Treatment and Assistance for Disasters. Social programs are carried out by the Komunitas Humaira Surakarta in order to increase the religious understanding of the congregation. The da'wah carried out by the Komunitas Humaira Surakarta is classified as tarqiyah da'wah, namely da'wah to increase the capacity of the people, faith and piety.